Preparation method and application of ferromanganese phosphate hydrate based on sulfate free radicals
By employing an oxidation-lock-release strategy based on sulfate radicals, manganese iron phosphate hydrate was prepared in aqueous solution, solving the problems of difficult Mn2+ oxidation and uneven element mixing. This enabled the preparation of a high-purity, low-cost manganese iron phosphate hydrate precursor, thereby improving the performance of lithium-ion battery cathode materials.
Patent Information
- Application Number
- CN202511326620.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2025-12-23
AI Technical Summary
Existing technologies for preparing manganese iron phosphate hydrate in aqueous solution suffer from problems such as difficulty and instability in Mn2+ oxidation, difficulty in uniformly mixing Mn/Fe elements, environmental pollution and high cost of traditional oxidants, making it difficult to prepare high-quality manganese iron phosphate hydrate precursors.
A three-step synergistic strategy based on sulfate radicals—oxidation-lock-release—was adopted. Sulfate radicals were generated by thermally activating persulfate as oxidants, which simultaneously oxidized Mn2+ and Fe2+ under acidic conditions to form a stable manganese iron-phosphate intermediate complex. The precipitation process was controlled by adjusting pH and temperature, thus preparing high-purity, uniformly composed manganese iron phosphate hydrate.
This study achieved the environmentally friendly and low-cost preparation of high-purity, uniformly composed manganese iron phosphate hydrate, which serves as a precursor for lithium-ion battery cathode materials. This improved electrochemical performance and cycle stability while reducing production costs and safety risks.
Smart Images

Figure CN121180966A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of lithium ion batteries, and particularly relates to a preparation method of a manganese iron phosphate hydrate based on sulfate radicals and application thereof. BACKGROUND
[0002] Lithium ion batteries, as a kind of efficient energy storage devices, have been widely used in the fields of portable electronic devices, electric vehicles and large-scale energy storage systems. Among them, the positive electrode material is one of the key components to determine the energy density, power density, cycle life and safety of lithium ion batteries. Among them, lithium manganese iron phosphate (LiMn 1-x Fe x PO4, especially when 0 < x ≤ 0.5) is expected to achieve higher energy density (theoretical energy density can reach about 580 Wh / kg) due to its combination of excellent cycle stability and cost advantage of lithium iron phosphate (LiFePO4) and relatively high operating voltage (about 4.1 V vs. Li / Li + ), and is considered as a potential lithium ion battery positive electrode material.
[0003] In the synthesis process of LiMn 1-x Fe x PO4, the physical and chemical properties of its precursor (such as phase purity, element distribution uniformity, particle size and distribution, morphology, etc.) have a decisive influence on the crystalline quality, microstructure and electrochemical performance of the final positive electrode material. Studies have shown that manganese iron phosphate hydrate (Mn 1-x Fe x PO4·H2O, 0 < x ≤ 0.5) is an ideal precursor for preparing LiMn 1- x Fe x PO4. In its unique crystal structure (usually monoclinic C2 / c space group), the lattice position occupied by the structure water molecule has structural similarity or relevance with the embedded position of lithium ions in the final product olivine structure LiMn 1-x Fe x PO4 (orthorhombic Pmna space group). This structural inheritance makes the crystal framework not need to undergo drastic reconstruction in the subsequent lithiation and high-temperature calcination process, which is beneficial to maintaining the integrity of the structure and reducing lattice defects, thereby helping to obtain LiMn 1-x Fe x PO4 positive electrode material with excellent electrochemical performance.
[0004] However, high-quality manganese iron phosphate hydrate Mn 1-x Fe x PO4·H2O is difficult to obtain, and the existing preparation methods have the problems of low yield, poor product quality, high cost, etc.Preparation of PO4·H2O (0 < x ≤ 0.5), especially in environmentally friendly and cost-controllable aqueous solution systems, faces many severe technical challenges:
[0005] (1) Mn 2+ Oxidation difficulties and Mn 3+ Instability
[0006] In aqueous solution systems, divalent manganese ions (Mn 2+ ) are difficult to be effectively oxidized to trivalent manganese ions (Mn 3+ ), even if Mn 3+ is generated, it is extremely unstable in aqueous solution, prone to disproportionation reaction (2Mn 3+ → Mn 2+ + MnO2↓) to generate MnO2 impurities or hydrolysis, resulting in decreased product purity and deteriorated performance.
[0007] (2) Difficulty in uniform mixing of Mn / Fe elements
[0008] Due to the differences in redox potential and reaction kinetics between Fe 2+ / Fe 3+ and Mn 2+ / Mn 3+ , in traditional co-precipitation methods, it is difficult to achieve uniform mixing of manganese and iron elements at atomic or molecular scale, and this non-uniformity will continue to the final LiMn 1-x Fe x PO4 product, resulting in partial manganese or iron enrichment, affecting the lithium ion intercalation and deintercalation kinetics and the overall performance of the material.
[0009] (3) Limitations of traditional oxidizing agents
[0010] ① Organic solvents and nitrate systems
[0011] To overcome the Mn 2+ oxidation problem, existing technologies (such as Adv. Mater. 23 (2011) 5050; Solid State Ionics 254 (2014) 72; J. Power Sources 247 (2014) 273; Part. Part. Syst. Charact. 40 (2023) 2300019) use nitrate (NO3 - ) as an oxidizing agent in organic solvents (such as ethanol). However, the use of organic solvents significantly increases production costs and poses safety hazards and environmental pressure for waste liquid treatment. More seriously, NO3 - produces toxic and harmful nitrogen oxides (NO x) gas, which pollutes the environment and does not meet the requirements of green chemistry and sustainable development.
[0012] ② Other problems of water phase oxidants
[0013] Chinese patent documents (such as publication numbers CN106981656A and CN113659134A) disclose the preparation of manganese iron phosphate hydrate in aqueous solution using hydrogen peroxide (H2O2), potassium permanganate (KMnO4), hypochlorite (such as NaClO), chlorate (such as KClO3), perchloric acid (HClO4), etc. as oxidants. However, these oxidants all have disadvantages, for example, H2O2 has relatively weak oxidation ability under acidic conditions, which may lead to insufficient oxidation (under-oxidation) of Mn 2+ ; KMnO4 is a strong oxidant itself, but it is easy to introduce K + impurities and is prone to over-oxidation, which can easily generate impurity phases such as MnO2; chlorine-containing oxidants (hypochlorite, chlorate, perchloric acid, etc.) can generate toxic gases such as Cl2 during the reaction process, which can introduce Cl-impurities.
[0014] (4) Existing water phase preparation processes have deficiencies
[0015] Some of the disclosed water phase preparation methods (such as Chinese patents with publication numbers CN104852037A, CN105514422A, CN104518217A, CN105244497A, and CN105449207A) still have problems such as difficulty in accurately controlling the macroscopic and microscopic uniformity of iron and manganese elements, easy introduction of impurities, long reaction time, high reaction temperature, high energy consumption, poor particle size uniformity of the product, and high requirements for equipment, etc.
[0016] In summary, the existing technology for preparing manganese iron phosphate hydrate Mn 1-x Fe x PO4·H2O in aqueous solution still faces great challenges in environmental protection, cost control, stability and accurate control of the product, phase purity and microstructure, especially how to achieve efficient and complete oxidation of Mn 2+ , how to prevent disproportionation and uneven precipitation of Mn 3c , how to ensure uniform mixing of Mn / Fe elements at atomic or molecular scale, while reducing environmental pollution and production costs to synthesize manganese iron phosphate hydrate Mn 1-x Fe x PO4·H2O. This is a key technical bottleneck restricting the development of high-performance manganese iron lithium phosphate positive electrode materials. Therefore, it is urgent to develop an environmentally friendly, low-cost, and mild process that can prepare high-quality Mn 1-x Fe x PO4·H2O with pure phase, uniform composition, and controllable structure. SUMMARY
[0017] Therefore, based on the above background, in order to overcome the technical problems of Mn 1- x Fe x PO4·H2O) in the prior art aqueous solution system, the present application provides a preparation method of manganese iron phosphate hydrate based on sulfate radicals and application thereof. 2≈ It is difficult to effectively oxidize, Mn 3≈ In the aqueous solution, Mn / Fe elements are difficult to achieve atomic-level uniform mixing, resulting in impure products, and traditional oxidizing agents (such as nitrate, chlorine-containing oxidizing agents) are prone to produce toxic and harmful gases or introduce impurities, organic solvent systems are high in cost and environmentally unfriendly, etc. Technical problems, the present application provides a preparation method of manganese iron phosphate hydrate based on sulfate radicals and application thereof, the present application innovatively puts forward a three-step synergistic strategy of "oxidation-locking-release based on sulfate radicals" to prepare the precursor manganese iron phosphate hydrate of the positive electrode material of lithium ion battery, which generates sulfate radicals (SO4 ·- ) with strong oxidizing property in situ through thermal activation of persulfate, and combines the formation and "locking" of the intermediate complex, and the final regulated "release" and uniform precipitation steps, to accurately prepare high-quality Mn 1-x Fe x PO4·H2O(0<x≤0.5).
[0018] The technical scheme provided by the present application is as follows:
[0019] A preparation method of manganese iron phosphate hydrate based on sulfate radicals, comprising the following steps:
[0020] S1: dissolving a manganese source compound, an iron source compound, a phosphorus source compound and a sulfate radical source compound in water to obtain a reaction solution;
[0021] S2: adjusting the pH of the reaction solution of step S1 to be acidic (for example, pH<3, preferably 0.5-2.0), heating and reacting for 0.2-2 hours to obtain a reaction solution containing an intermediate complex;
[0022] S3: adjusting the pH of the intermediate complex reaction solution obtained in step S2 to 1-3, heating and continuing to react for 0.5-3 hours to obtain a reaction solution with precipitate;
[0023] S4: performing solid-liquid separation on the reaction solution with precipitate obtained in step S3 to collect the precipitate;
[0024] After the precipitate is washed with deionized water, the precipitate is re-dispersed in a phosphoric acid solution with a pH value of 1-3 to obtain a suspension; then the temperature of the suspension is controlled at 60-100℃, and the suspension is crystallized and aged for 2-12 hours under stirring;
[0025] S5: solid-liquid separation is performed on the suspension after crystallization and aging in step S4, and the separated crystal precipitate is washed and dried to obtain the manganese iron phosphate hydrate Mn 1-x Fe x PO4·H2O (0 < x ≤ 0.5).
[0026] Preferably, the manganese source compound in step S1 is at least one selected from manganese sulfate, manganese halide (e.g. manganese chloride), manganese acetate; the iron source compound is at least one selected from ferrous sulfate, ferrous halide (e.g. ferrous chloride), ferrous acetate; the phosphorus source compound is at least one selected from phosphoric acid, monoammonium phosphate, diammonium phosphate; and the sulfate radical source compound is at least one selected from sodium persulfate, ammonium persulfate, potassium persulfate.
[0027] Preferably, in step S1, the molar ratio of Mn, Fe, P and S derived from the sulfate radical source compound in the reaction solution is Mn:Fe:P:S = (1-x):x:(1.0-1.5):(1.0-2.0), wherein 0 < x ≤ 0.5.
[0028] Preferably, the heating temperature in step S2 is 60-100℃.
[0029] Preferably, the heating temperature in step S3 is 60-100℃.
[0030] Preferably, the pH value adjusting agent is one or more selected from sulfuric acid, phosphoric acid, ammonia water, sodium hydroxide.
[0031] Based on the same inventive concept, the application further provides a manganese iron phosphate hydrate prepared by the above-mentioned method for preparing a sulfate radical-based manganese iron phosphate hydrate.
[0032] Based on the same inventive concept, the application further provides an application of the manganese iron phosphate hydrate prepared by the above-mentioned method for preparing a sulfate radical-based manganese iron phosphate hydrate as a precursor for preparing a lithium ion battery cathode material.
[0033] Further, the lithium ion battery cathode material is LiMn 1-x Fe x PO4 / C or NaMn 1-x Fe x PO4 / C composite cathode material, wherein 0 < x ≤ 0.5.
[0034] Based on the same inventive concept, the application also provides a LiMn 1-x Fe x A preparation method of a PO4 / C composite positive electrode material, comprising the following steps:
[0035] ①Take the manganese iron phosphate hydrate prepared by the preparation method of the manganese iron phosphate hydrate based on sulfate radical, a lithium source compound and a carbon source, and mix them to obtain a mixed powder;
[0036] Take the manganese iron phosphate hydrate and the lithium source compound according to a Li:(Mn+Fe) molar ratio of (1-1.1):1;
[0037] The addition amount of the carbon source is 5-30 wt% of the sum of the manganese iron phosphate hydrate and the lithium source compound;
[0038] ②Subsection high-temperature calcination is performed on the mixed powder in step ① under an inert or reducing atmosphere, and after the calcination is completed, the product is naturally cooled to room temperature in an inert atmosphere to obtain a LiMn 1-x Fe x PO4 / C(0<x≤0.5) composite positive electrode material.
[0039] Further, the subsection high-temperature calcination in step ② is specifically as follows: the mixed powder is heated to 300-370℃ at a uniform heating rate, and then heated to 550-800℃ at a uniform heating rate, and after a certain time of heat preservation, the product is cooled.
[0040] Further, the lithium source compound is at least one of lithium hydroxide monohydrate and lithium carbonate;
[0041] The carbon source is at least one of organic substances such as glucose, sucrose and citric acid, or a conductive carbon material.
[0042] The application has the following beneficial effects:
[0043] The application is based on the synergistic strategy of oxidation-locking-releasing of sulfate radicals to prepare a manganese iron phosphate hydrate Mn 1-x Fe x PO4·H2O(0<x≤0.5) and has the following excellent effects:
[0044] (1) Environment-friendly and cost-effective
[0045] The preparation of the manganese iron phosphate hydrate is based on a water solution system, which can avoid the use of expensive, flammable and explosive and volatile organic solvents such as ethanol, can significantly reduce the production cost and safety risk, and is also conducive to reducing the subsequent waste liquid treatment cost.
[0046] The sulfate radical source compound used in the application has strong oxidation ability, and its reduction product is sulfate (SO4 2- ), which is environmentally friendly, and can fundamentally avoid the environmental pollution problem of toxic and harmful gases such as NOx generated by using nitrate oxidants or Cl2 generated by using chlorine-containing oxidants compared with the prior art. At the same time, the problem of Mn 2+ under-oxidation caused by the insufficient oxidation ability of hydrogen peroxide under acidic conditions or the problem of excessive oxidation of potassium permanganate to generate impurities such as MnO2 can also be effectively avoided.
[0047] (2) The product composition, purity and structure are accurately controllable
[0048] The oxidant sulfate radical in the application needs to be thermally activated at a specific temperature to be effectively formed, so that the manganese source, iron source and phosphorus source and other raw materials can be fully and uniformly mixed in the solution before the oxidation reaction occurs.
[0049] And the unique "oxidation-locking-release" three-step regulation strategy of the application, especially the formation of the intermediate manganese iron phosphate complex and the stable "locking" effect of the P-O bond, can effectively inhibit the disproportionation and premature precipitation of Mn 3+ , and ensure the synchronous, complete and uniform oxidation of Mn 2+ / Fe 2+ . Then through the accurate regulation of subsequent pH and temperature, the manganese iron phosphate hydrate product with uniform distribution of elements according to the stoichiometric ratio (atomic / molecular level mixing), pure phase (for example, pure phase monoclinic C2 / c space group), and regular morphology (for example, micron-sized particles formed by agglomeration of nanoparticles) can be prepared.
[0050] And the data of the examples show that the Mn, Fe content, crystallization water content and P / (Mn+Fe) molar ratio of the manganese iron phosphate hydrate product prepared by the application are very close to the theoretical value, which shows excellent stoichiometric control accuracy and high purity.
[0051] (3) The prepared positive electrode material has excellent electrochemical performance
[0052] The high-quality manganese iron phosphate hydrate with high purity, high uniformity of manganese and iron elements and excellent crystal structure prepared by the application can lay a solid foundation for the subsequent preparation of high-performance LiMn 1-x Fe x PO4 / C (0<x≤0.5) positive electrode material as a precursor.
[0053] As can be seen from the examples, the LiMn 0.6 Fe 0.4PO4 / C positive electrode material exhibits very excellent first discharge specific capacity (e.g. up to 144 mAh / g at 1C rate) and excellent cycle stability (e.g. capacity retention rate up to 95% after 200 cycles at 1C rate), even for high Fe content LiMn 0.5 Fe 0.5 PO4 / C, the capacity can reach 151 mAh / g at 1C rate, and the capacity retention rate is as high as 97% after 200 cycles.
[0054] (4) The process is simple, easy to scale up, and has industrialization potential
[0055] The reaction conditions adopted in the present application are relatively mild (the reaction temperature is usually in the range of 60-100 DEG C), the operation process is simple, and the raw materials (such as persulfate, manganese sulfate, ferrous sulfate, phosphoric acid, etc.) are all bulk chemical products, which are low in cost and easy to obtain. The entire process is easy to control, has good reproducibility, and has good prospects for scale-up production and industrial application.
[0056] In summary, the method for preparing high-performance manganese iron phosphate hydrate (Mn 1-x Fe x PO4·H2O) based on sulfate radical in the present application provides a new approach for the preparation of precursor with economic feasibility, environmental friendliness, efficient process and highly controllable product quality, which is beneficial to the development and popularization of lithium batteries.
[0057] Drawings
[0058] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings needed to be used in the embodiments or prior art description will be briefly introduced below. It should be understood that the drawings described below are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor on the basis of these drawings.
[0059] Figure Figure 1 The preparation of the manganese iron phosphate hydrate precursor (Mn 1-x Fe x PO4·H2O) of the present application and its conversion into LiMn 1-x Fe x PO4 / C positive electrode material; wherein the figure Figure 1 The "oxidation-locking-release" chemical conversion process based on sulfate radical of the core of the present application is schematically shown.
[0060] Figure Figure 2 Mn 0.6 Fe 0.4PO4-H2O precursor and LiMn 0.6 Fe 0.4 PO4 / C cathode material:
[0061] wherein:
[0062] Figure 1 Figure 2 (a) is a SEM image of the Mn 0.6 Fe 0.4 PO4-H2O precursor as prepared, showing the overall morphology of its secondary particles;
[0063] Figure 2 Figure 2 (b) is a TEM image of the Mn 0.6 Fe 0.4 PO4-H2O precursor as prepared, showing the morphology and size of its primary particles;
[0064] Figure 3 Figure 2 (c) is a HRTEM image of the Mn 0.6 Fe 0.4 PO4-H2O precursor as prepared, showing the lattice fringes thereof;
[0065] Figure 4 Figure 2 (d) is an XRD pattern of the Mn 0.6 Fe 0.4 PO4-H2O precursor as prepared, containing the standard card of phosphate monoclinic crystal system C2 / c space group (e.g. JCPDS No. 78-1082 or similar) as reference, for confirming the phase purity and crystal structure thereof;
[0066] Figure 5 Figure 2 (e) is a SEM image of the LiMn 0.6 Fe 0.4 PO4 / C cathode material as prepared from the Mn 0.6 Fe 0.4 PO4-H2O precursor, showing the morphology thereof after calcination;
[0067] Figure 6 Figure 2 (f) is a TEM image of the LiMn 0.6 Fe 0.4 PO4 / C cathode material as prepared from the Mn 0.6 Fe 0.4 PO4-H2O precursor, showing the microstructure details thereof;
[0068] Figure 7 Figure 2 (g) is a TEM image of the LiMn 0.6 Fe 0.4 PO4 / C cathode material as prepared from the Mn0.6 Fe 0.4 HRTEM images of PO4 / C cathode material can show its lattice fringe and possible surface carbon coating layer;
[0069] Figure 1 Figure 2 (h) is the first charge-discharge curve of the LiMn 0.6 Fe 0.4 PO4·H2O as precursor prepared LiMn 0.6 Fe 0.4 XRD pattern of PO4 / C cathode material can show that it is the target orthorhombic Pmna space group olivine structure.
[0070] Figure 1 Figure 3 LiMn 0.6 Fe 0.4 PO4 / C cathode material prepared by Example 1, wherein:
[0071] Figure 1 Figure 3 (a) is the first charge-discharge curve of the button cell showing its initial capacity and voltage plateau characteristics in the voltage range of 2.5-4.5 V (vs. Li / Li + );
[0072] Figure 1 Figure 3 (b) is the cycle performance curve of the button cell showing the change of capacity retention rate with cycle number, used to evaluate its cycle stability. DETAILED DESCRIPTION
[0073] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0074] The present application first proposes a three-step synergistic strategy of "oxidation-locking-release based on sulfate radical", to prepare manganese iron phosphate hydrate (Mn 1-x Fe x PO4·H2O, 0<x≤0.5) which is prepared by using in-situ generated sulfate radical (SO4 ·- ) with strong oxidizing property as oxidant in aqueous solution system to prepare manganese iron phosphate hydrate (Mn 1-x Fe xPO4-H2O, 0 < x < 0.5), the core reaction mechanism and the process of preparing manganese iron phosphate hydrate as a precursor to prepare cathode material as shown in Figure 1 as follows:
[0075] (1) Formation of sulfate radical (SO4 ·- )
[0076] In the acidic aqueous solution, by heating (for example, 60-100℃), the homolytic cleavage of the peroxide bond (-O-O-) in persulfate (M2S2O8, where M is NH4 + , Na + , K + , etc.) occurs, producing a very active sulfate radical (SO4 ·- ). The process can be simplified as: S2O8 2- + heat → 2SO4 ·- , SO4 ·- radical has a very high oxidation potential (E 0 (SO4 ·- / SO4 2- ) ≈ 2.5-3.1V vs. NHE), much higher than conventional oxidants such as H2O2.
[0077] (2) Simultaneous oxidation of Mn 2+ / Fe 2+
[0078] The in-situ generated SO4 ·- radical can rapidly and effectively oxidize the coexisting Fe 2+ and Mn 2+ ions in the solution to Fe 3+ and Mn 3+ . Due to the strong oxidizing property of SO4 ·- , even for the relatively difficultly oxidized Mn 2+ , high-efficiency conversion can be achieved. The oxidation reaction can be schematically represented as: (1-x)Mn 2+ +xFe 2+ +SO4 ·- → (1-x)Mn 3+ +xFe 3+ +SO4 2- The key of this process lies in the simultaneous oxidation, which helps the subsequent uniform mixing of manganese and iron elements.
[0079] (3) “Locking” of high-valence manganese iron ions — formation of intermediate state complex
[0080] In the acidic phosphate system (for example, H2PO4 - / HPO4 2- ), newly generated, highly reactive Fe 3+ and Mn 3+ can immediately interact with phosphate ions in solution through strong P-O coordination bonds to form soluble, relatively stable intermediate manganese-iron-phosphate complexes. It is postulated that complexes such as [Mn 1-x Fe x (H2PO4) y ] z+ are formed. This complexation effectively "locks" the high valence state of manganese and iron ions, with dual key roles:
[0081] a) By inhibiting disproportionation of Mn 3+ , the stability of Mn 3+ in aqueous solution is significantly enhanced, effectively preventing its disproportionation reaction (2Mn 3+ → Mn 2+ + MnO2↓) to form MnO2impurities.
[0082] b) By ensuring elemental homogeneity, Fe 3+ / Mn 3+ can be prevented from heterogeneous or selective precipitation due to differences in solubility product or hydrolysis rates, thereby ensuring atomic / molecular level homogeneity of manganese and iron elements in solution and even in subsequent precipitated products.
[0083] Its locking reaction (using H2PO4 - as the primary phosphorus species as an example) can be schematically represented as: (1-x)Mn 3+ +xFe 3+ +yH2PO4 - → [Mn 1-x Fe x (H2PO4) y ] z+ (where y is the coordination number and z is the charge number of the complex, both depending on the specific pH and concentration conditions)
[0084] (4) Regulated "release" of intermediate complexes - Mn 1-x Fe x PO4-H2O homogenous precipitation formation
[0085] By precisely regulating the pH (typically slightly increasing the pH to the weakly acidic range, e.g., pH 1-3, relative to the oxidation-locking step) and / or temperature of the solution, the stability of the manganese-iron-phosphate intermediate complexes can be altered, prompting their controlled dissociation, hydrolysis, or ligand exchange, gradually releasing H + and / or partially excess coordinated phosphate, thereby allowing Mn 1-x Fe xPO4·H2O is precipitated in the form of fine and uniform precipitate particles. This controlled release ensures the slow and uniform precipitation process, which is beneficial to the formation of primary products with uniform particle size and regular morphology. The release reaction can be schematically represented as a simplified representative process: [Mn 1-x Fe x (H2PO4) y ] z+ + H2O → Mn 1-x Fe x PO4·H2O↓ + (y-1) H2PO4 - + m H + (m is the number of released protons)
[0086] (5) Crystal growth and ripening of the crystal
[0087] The newly formed amorphous or microcrystalline Mn 1-x Fe x PO4·H2O is precipitated at a suitable pH (such as a phosphoric acid solution with pH 1-3) and temperature (such as 60-100℃) for a specific time of ripening and crystallization process. In this process, through the Ostwald ripening effect, small grains dissolve and large grains grow, and at the same time, lattice defects are repaired, finally forming Mn 1-x Fe x PO4·H2O crystals with more complete crystal form, more uniform particle size distribution and higher purity.
[0088] The technical solutions of the present application are described in detail below.
[0089] (1) The preparation method of the sulfate radical-based manganese iron phosphate hydrate (Mn 1-x Fe x PO4·H2O, 0 < x ≤ 0.5) of the present application, comprising the following steps:
[0090] S1: Dissolving a manganese source compound, an iron source compound, a phosphorus source compound and a sulfate radical source compound in water to obtain a reaction solution;
[0091] In this step, the target product Mn 1-x Fe xThe stoichiometric ratio of Mn and Fe in MnPO4·H2O (1-x):x, and the preset molar ratio of P / (Mn+Fe) (for example 1.0-1.5, preferably 1.05-1.2) and S / (Mn+Fe) (where S is derived from a sulfate radical source compound, for example 1.0-2.0, preferably 1.0-1.5), the corresponding manganese source compound (such as one or more of manganese sulfate, manganese chloride, manganese acetate), iron source compound (such as one or more of ferrous sulfate, ferrous chloride, ferric acetate), phosphorus source compound (such as one or more of 85wt% H3PO4 aqueous solution, NH4H2PO4, (NH4)2HPO4) and sulfate radical source compound (such as one or more of Na2S2O8, (NH4)2S2O8, K2S2O8) are weighed, and the above weighed raw materials are sequentially or simultaneously dissolved in deionized water, and stirred at room temperature (for example using a magnetic stirrer or a mechanical stirrer) until a clear and uniform reaction solution is formed, so that the total ion concentration of (Mn+Fe) in the final solution is 0.1-1.0M.
[0092] S2: After adjusting the pH of the reaction solution of step S1 to be acidic, heating is carried out to obtain a reaction solution containing an intermediate complex;
[0093] This step is the core step of the preparation of the present application, which involves the generation of sulfate radicals, the simultaneous oxidation of Fe 2+ and Mn 2+ ions and the locking reaction
[0094] Specifically, the pH value of the reaction solution obtained in step S1 is adjusted to the acidic range (for example pH<3, preferably in the range of 0.5-2.0) using a pH adjuster (for example one or more of H2SO4 solution (mass concentration 50%), H3PO4 solution (mass concentration 85%), or NH3·H2O solution (mass concentration 25%), NaOH solution (mass concentration 30%)). Then the pH-adjusted reaction solution is transferred to a reaction vessel (for example a three-necked flask, a jacketed reactor) with stirring device and temperature control system, heated to the target reaction temperature (for example 60-100℃, preferably 70-90℃) at a certain heating rate, and stirred at constant temperature for a period of time (for example 0.2-2 hours, preferably 0.5-1.5 hours). In this process, persulfate is decomposed by heat to generate active sulfate radicals, which in turn efficiently and simultaneously oxidize Mn 2+ and Fe 2+ to Mn 3+ and Fe 3+ , while the newly generated Mn 3+ and Fe 3+ rapidly form stable manganese-iron-phosphate intermediate complexes with phosphorus species.
[0095] Specifically, in this step, the pH value of the reaction solution is adjusted to strong acidity, and the reaction is carried out at a specific heating temperature. Specifically, the reaction is as follows: under this condition, the S2O8 2- radical source compound (such as persulfate) is activated by heat, and the peroxide bond (-O-O-) is homolytically cleaved, producing a sulfate radical SO4 0 with extremely strong activity (standard electrode potential E ·- (SO4 2- / SO4 ·- ≈2.5-3.1V vs. NHE), a moderate half-life (for example, about 30-40μs in aqueous solution), which in-situ generated SO4 ·- radicals will oxidize Mn 2+ and Fe 2+ in the solution to Mn 3+ and Fe 3+ at the same time;
[0096] The core is that the newly generated Mn 3+ and Fe 3+ can rapidly react with the phosphorus source compounds (such as H2PO4 - or HPO4 2- phosphorus species dissociated from H3PO4) present in the acidic medium to form a relatively stable and soluble manganese-iron phosphate intermediate complex (presumably in the form of [Mn 1-x Fe x (H2PO4) y ] z+ and the like), which effectively "locks" the high-valence manganese and iron ions. This in-situ formed complexation not only inhibits the disproportionation reaction and hydrolysis of Mn 3+ , but also avoids the premature or uneven precipitation of Mn 3+ and Fe 3+ due to differences in solubility or hydrolysis rate, thereby ensuring the uniform dispersion of Mn 1-x and Fe x in solution and the homogeneity of subsequent reactions, and laying the foundation for the atomic-level uniform distribution of manganese and iron elements in the final product.
[0097] S3: After adjusting the pH of the reaction solution of the intermediate complex obtained in step S2 to 1-3, heating and continuing the reaction, a reaction solution with precipitate is obtained;
[0098] In this step, the release is regulated so that the initial product Mn 1-x Fe xPO4-H2O can be precipitated uniformly, specifically, the reaction solution containing the intermediate state complex obtained after the reaction of step S2 is adjusted slowly to the target range (for example, pH 1-3, preferably 1.0-2.0) in pH value again using a pH adjuster (usually an alkaline adjuster such as NH3-H2O solution or NaOH solution (NH3-H2O solution (25% by mass), NaOH solution (30% by mass)) to raise the pH value. Then the reaction is continued to be stirred at the same or adjusted temperature (for example, 60-100°C, preferably 70-90°C) for a period of time (for example, 0.5-3 hours, preferably 1-2.5 hours) to promote the controlled conversion of the intermediate state complex, to promote the gradual controlled hydrolysis or ligand exchange thereof, to release H + and / or part of the excess coordinated phosphate, so as to form the primary product manganese iron phosphate hydrate (Mn 1-x Fe x PO4-H2O, 0
[0099] S4: the reaction solution with precipitate obtained in step S3 is subjected to solid-liquid separation, and the precipitate is collected;
[0100] After the precipitate is washed with deionized water, it is re-dispersed in a phosphoric acid solution with a pH value of 1-3 to obtain a suspension. Then the temperature of the suspension is controlled at 60-100°C, and crystallization and aging are carried out under stirring;
[0101] Specifically, the suspension (reaction solution) containing the manganese iron phosphate hydrate precipitate formed in step S3 is subjected to solid-liquid separation (for example, by vacuum filtration, centrifugal separation or the like), and then the obtained wet cake (precipitate) is washed with deionized water and re-dispersed in a specific phosphoric acid solution (the concentration of phosphoric acid can be 0.01-0.5M) with a specific pH value (for example, pH 1-3, preferably 1.0-2.5, which can be adjusted by adding H3PO4 or NH3-H2O / NaOH) to form a suspension with a certain solid content. The suspension is subjected to crystallization and aging treatment for a certain time (for example, 2-12 hours, preferably 4-10 hours) at a specific temperature (for example, 60-100°C, preferably 70-90°C) under continuous stirring, which helps to dissolve small crystal grains, grow large crystal grains (Ostwald ripening effect), and repair lattice defects, so as to obtain Mn 1-x Fe x PO4-H2O crystals, aiming to improve the crystallinity of the product, repair lattice defects, and make the particle size distribution more uniform through Ostwald ripening.
[0102] S5: solid-liquid separation is performed on the suspension after crystallization and ripening in step S4, and the separated crystal precipitate is washed and dried, to obtain the manganese iron phosphate hydrate Mn 1-x Fe x PO4·H2O (0 < x ≤ 0.5).
[0103] This step is a post-processing step. Specifically, the product suspension after crystallization and ripening in step S4 is subjected to solid-liquid separation, and the obtained filter cake is repeatedly washed several times (for example, 3-5 times) with deionized water until the washing liquid is substantially free of SO42- (or the conductivity is close to that of deionized water) as detected by a BaCl2 solution, so as to completely remove the surface-adsorbed impurity ions and residual reaction mother liquor. Then, the washed crystals can be optionally washed 1-2 times with anhydrous ethanol to facilitate subsequent drying. Finally, the washed and dried crystals are dried in a vacuum oven or a forced air drying oven at a suitable temperature (for example, 60-100°C, preferably 80°C) for a period of time (for example, 8-24 hours, preferably 12 hours, or until a constant weight is reached), to obtain the final powder-like manganese iron phosphate hydrate Mn 1-x Fe x PO4·H2O (0 < x ≤ 0.5).
[0104] The present application also provides a method for preparing a manganese iron phosphate hydrate as a precursor for preparing a LiMn 1-x Fe x PO4 / C positive electrode material, comprising the following steps:
[0105] ①Taking a manganese iron phosphate hydrate prepared by a method for preparing a manganese iron phosphate hydrate based on a sulfate radical, a lithium source compound, and a carbon source, and mixing them to obtain a mixed powder;
[0106] The manganese iron phosphate hydrate and the lithium source compound are taken in a Li:(Mn+Fe) molar ratio of (1-1.1):1;
[0107] The addition amount of the carbon source is 3-30wt% of the sum of the manganese iron phosphate hydrate and the lithium source compound;
[0108] Specifically, the manganese iron phosphate hydrate Mn 1-x Fe x PO4·H2O precursor powder, a lithium source compound (for example, lithium hydroxide monohydrate LiOH·H2O, which is usually configured in a Li:(Mn+Fe) molar ratio of 1:1 or slightly excessive), and a carbon source (for example, an organic substance such as glucose, sucrose, citric acid, etc., which is usually added in an amount of 10-20wt% of the total mass of the precursor and the lithium source, for example, 15wt%) are uniformly mixed (for example, by ball milling).
[0109] ②mixing powder in step 1 is subjected to high-temperature calcination in stages under an inert or reducing atmosphere, and after the calcination is completed, the product is naturally cooled to room temperature in an inert atmosphere, to obtain LiMn 1-x Fe x PO4 / C (0 < x < 0.5) composite positive electrode material.
[0110] Specifically, the uniformly mixed powder is subjected to high-temperature calcination in stages under an inert atmosphere (such as N2 or Ar atmosphere) or reducing atmosphere. For example, the powder can be first heated to a lower pre-calcination temperature (such as 350°C) at a certain heating rate (such as 5°C / min) and kept at this temperature for a period of time (such as 2 hours), with the purpose of preliminary decomposition of the carbon source and preliminary reaction with the precursor and lithium salt; then heated to a higher final calcination temperature (such as 550-800°C, the specific temperature is usually optimized according to the value of x and the desired grain size / carbon layer quality, generally speaking, the larger the value of x, i.e. the higher the Fe content, the higher the required calcination temperature) at the same or different heating rate, and kept at this temperature for a long time (such as 10 hours) to complete the lithiation reaction, crystal growth and carbon coating process. After the calcination is completed, the product is naturally cooled to room temperature in an inert atmosphere, to obtain LiMn 1-x Fe x PO4 / C composite positive electrode material.
[0111] (3) The specific operations of the characterization involved in the following examples are shown below
[0112] ①Electrochemical performance test
[0113] The LiMn 1-x Fe x PO4 / C active positive electrode material prepared by the present application, a conductive agent (such as acetylene black, SuperP, etc. carbon material) and a binder (such as polyvinylidene fluoride PVDF) are uniformly mixed (such as by magnetic stirring or planetary ball milling) in a certain mass ratio (such as 8:1:1) in N-methyl-2-pyrrolidone (NMP) solvent to form an electrode slurry with suitable viscosity. The slurry is uniformly coated on an aluminum foil current collector (pre-cleaned), and the coating thickness is controlled to obtain the target surface density. The aluminum foil coated with the slurry is first dried at a lower temperature (such as 60°C) to remove most of the solvent, and then thoroughly dried (such as 12 hours) in a vacuum oven at a higher temperature (such as 120°C). The dried electrode is rolled (to increase the compaction density and improve the conductive contact), and then punched into a specific size of circular electrode (such as 14mm in diameter) as the working electrode.
[0114] A lithium metal sheet was used as both the counter electrode and the reference electrode, a microporous polypropylene or polyethylene-based separator (e.g., Celgard 2400) was used as the separator, and a solution of 1 mol / L LiPF6dissolved in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) (e.g., in a volume ratio of 1:1:1) was used as the electrolyte.
[0115] A CR2032 button cell was assembled in a glove box filled with high-purity inert gas (e.g., argon or nitrogen, water and oxygen content <0.1 ppm) in the order of positive electrode sheet / separator / lithium sheet.
[0116] Constant current charge-discharge tests were performed at room temperature (e.g., 25°C) using a multi-channel battery test system (e.g., Neware BTS series). The test voltage range was usually set to 2.5-4.5 V (vs. Li / Li + ). Unless otherwise specified, the current density of 1C was defined as the current value corresponding to the complete release or intercalation of one electron per (Mn+Fe) atom in LiMn 1-x Fe x PO4 / C within 1 hour. Both the capacity and the current were calculated based on the active material LiMn 1- x Fe x PO4 / C. The cycle life test was usually performed at a specific C rate, and the capacity change with the number of cycles was recorded.
[0117] Example 1: Mn 0.6 Fe 0.4 PO4·H2O and LiMn 0.6 Fe 0.4 PO4 / C positive electrode material
[0118] (1) Mn 0.6 Fe 0.4 PO4·H2O preparation
[0119] According to the molar ratio of Mn:Fe:P:S = 0.6:0.4:1.1:1.2, analytical pure manganese sulfate monohydrate (MnSO4·H2O), ferrous sulfate heptahydrate (FeSO4·7H2O), 85wt% phosphoric acid (H3PO4) aqueous solution, and ammonium persulfate ((NH4)4S2O8) were weighed. These raw materials were dissolved in an appropriate amount (so that the final total ion concentration of (Mn+Fe) was 0.1-1.0 M) of deionized water, and stirred to form a uniform reaction solution.
[0120] 25wt% ammonia water (NH c• H2O) to adjust the pH value of the reaction solution to 0.5. The pH-adjusted reaction solution was transferred to a 500 mL three-necked flask with magnetic stirring and water bath heating, heated to 80 °C and kept at this temperature for 1 hour of vigorous stirring (this is the radical generation-oxidation-locking step).
[0121] After the reaction was completed, 25 wt% ammonia water was continuously added slowly to the reaction solution to further adjust its pH value to 1.5. Then the reaction was continuously stirred at 80 °C for 2 hours (this is the release-precipitation step).
[0122] After the reaction was completed, the obtained suspension was subjected to solid-liquid separation by vacuum filtration to obtain a wet precipitate (filter cake). After washing the filter cake with deionized water, it was re-dispersed in a phosphoric acid solution with a pH value of 1.5 (the phosphoric acid solution was prepared by adding an appropriate amount of 85% H3PO4 and deionized water, and the concentration of phosphoric acid was about 0.1 M), with a solid content of about 10 wt%, and was subjected to crystallization and aging treatment at 80 °C for 8 hours to obtain a suspension with a solid content of about 10 wt% (this is the crystallization-aging step). Finally, the suspension after crystallization and aging was filtered again, washed repeatedly with deionized water until no obvious white precipitate was observed in the washing liquid when tested with a BaCl2 solution, and then washed twice with anhydrous ethanol. The washed filter cake was dried in a vacuum oven at 80 °C for 12 hours to obtain Mn 0.6 Fe 0.4 PO4·H2O as a light brown powder.
[0123] The morphology of the prepared Mn 0.6 Fe 0.4 PO4·H2O was observed by scanning electron microscopy (SEM, FEI Quanta 250). The results are shown in Figure 2 (a) ~ Figure 2 (c), which showed that the Mn 0.6 Fe 0.4 PO4·H2O was mainly composed of micron-sized (diameter about 1-5 μm) secondary particles formed by the agglomeration of sub-micron or nano-sized (diameter about 50-200 nm) primary particles, and the particle morphology was relatively regular and the distribution was relatively uniform; the crystal structure was analyzed by X-ray diffraction (XRD, Bruker D8 Advance, Cu Kα radiation, ), and the results are shown in Figure 2 (d), which showed that the XRD pattern of the Mn 0.6 Fe 0.4 PO4·H2O could be well matched with the characteristic peak positions of the standard card of the monoclinic crystal system C2 / c space group of phosphate (PDF # 78-1082 of MnPO4·H2O), indicating that the pure phase Mn 0.6 Fe0.4 PO4-H2O, no obvious diffraction peaks of MnO2, Fe2O3 or other impurity phases were observed. The elemental analysis results (the contents of metal elements Mn and Fe were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES), the content of P was determined by ion chromatography or gravimetric method, and the content of crystal water was determined by thermogravimetric analysis (TG-DSC) under N2 atmosphere at a temperature rising rate of 10°C / min to, for example, 600°C) showed that the Mn 0.6 Fe 0.4 PO4-H2O had a Mn content of 19.1wt%, a Fe content of 13.5wt%, a molar ratio of P / (Mn+Fe) of 0.99, and a crystal water content (calculated from the weight loss in the range of about 150-350°C according to the TG curve) of 10.9wt%. These experimentally determined values were very close to the theoretical chemical composition of Mn 0.6 Fe 0.4 PO4-H2O (theoretical values: Mn about 18.77wt%, Fe about 13.35wt%, P about 17.66wt% (corresponding to P / (Mn+Fe)=1), H2O about 10.27wt%), further confirming the accuracy of the present application in controlling the stoichiometry of the product and the high purity of the product.
[0124] (2) The Mn 0.6 Fe 0.4 PO4-H2O powder prepared above was used to prepare LiMn 0.6 Fe 0.4 PO4 / C cathode material
[0125] The prepared Mn 0.6 Fe 0.4 PO4-H2O powder, lithium hydroxide monohydrate (LiOH-H2O, analytical pure), and glucose (C6H 12 O6, analytical pure, as a carbon source) were accurately weighed according to a Li:(Mn+Fe) molar ratio of 1.02:1, and the mass of glucose accounted for 15wt% of the total mass of the Mn 0.6 Fe 0.4 PO4-H2O precursor and LiOH-H2O. The three were thoroughly ground and mixed in an agate mortar (about 30 minutes), or a planetary ball mill (for example, QM-3SP4, Nanjing University Instrument Factory) was used in anhydrous ethanol medium, zirconium oxide balls were used (ball-to-material mass ratio of 10:1), and the mixed powder was obtained by ball milling at a speed of 300rpm for 4 hours.
[0126] The uniformly mixed powder was transferred to a corundum ceramic boat and placed in a tube furnace for two-stage calcination under the protection of flowing N2 atmosphere (high-purity nitrogen gas, flow rate of about 100mL / min).
[0127] The calcination procedure was as follows: first, the temperature was raised from room temperature to 350°C at a rate of 5°C / min, and then kept at 350°C for 2 hours (pre-calcination stage); then, the temperature was raised from 350°C to 650°C at a rate of 5°C / min, and then kept at 650°C for 10 hours (final calcination stage). After the calcination, the product was taken out and gently ground under N2 atmosphere, to obtain black LiMn 0.6 Fe 0.4 PO4 / C composite cathode material.
[0128] The morphology of the prepared LiMn 0.6 Fe 0.4 PO4 / C cathode material was observed by SEM, and the results are shown in Figure 2 (e), and Figure 2 The SEM photos of (e) show that the LiMn 0.6 Fe 0.4 PO4 / C material presents micron-sized secondary particles formed by the agglomeration of nano-sized (about 50-150 nm) primary particles, which to some extent inherits the characteristics of the precursor, but the particle surface is more compact or is coated by a uniform carbon layer.
[0129] Figure 2 (f) and Figure 2 (g) are the TEM and HRTEM of the LiMn 0.6 Fe 0.4 PO4 / C cathode material. The clear lattice fringes (for example, corresponding to the specific interplanar spacing of the olivine structure) can be observed, which confirms the good crystallinity of the LiMn 0.6 Fe 0.4 PO4 / C cathode material, and the amorphous or partially graphitized carbon coating layer with a thickness of about 2-5 nm can be observed on the surface of the particles. The crystal structure of the LiMn 0.6 Fe 0.4 PO4 / C cathode material was analyzed by XRD, and the results are shown in Figure 2 (h). The XRD pattern of the LiMn 0.6 Fe 0.4 PO , / C material can be well matched with the standard card (JCPDS No. 74-0375) of the typical olivine structure orthorhombic Pmna space group LiMnPO4, indicating that the target phase of the highly crystalline lithium manganese iron phosphate material is successfully synthesized by the precursor and the optimized calcination process, and there is no obvious impurity phase (such as metal oxide, other phosphate phase or unreacted lithium salt).
[0130] (3) The LiMn 0.6 Fe 0.4Electrochemical performance of PO4 / C cathode material was tested
[0131] CR2032 button cells were assembled (active material: Super P: PVDF = 80:10:10, surface loading about 2 mg / cm 2 ) according to the specific operation of the above electrochemical performance test, and the electrochemical performance test was performed using a Neware battery test system (e.g. BTS-5V10mA). Figure 3 (a) shows the first charge-discharge curve of LiMn 0.6 Fe 0.4 PO4 / C as the cathode active material, at 25℃, 2.5-4.5V (vs. Li / Li + ) voltage window, 1C (1C current density is 170mA / g calculated based on the theoretical capacity of 170mAh / g) current density. As can be seen from the figure, the material exhibits clear Mn 2+ / Mn 3+ (about 4.0-4.2V) and Fe 2+ / Fe 3+ (about 3.4-3.6V) charge-discharge platforms, with a first discharge specific capacity as high as 144mAh / g (about 84.7% of the theoretical capacity). Figure 3 (b) shows the results of the cycle performance test of the battery at 1C rate. After 200 charge-discharge cycles, the capacity retention rate is still as high as 95%, and the coulombic efficiency is close to 100%, showing excellent cycle stability.
[0132] Example 2: Investigate the influence of different pH adjusters, raw materials and proportions on the performance of Mn 0.6 Fe 0.4 PO4·H2O precursor and LiMn 0.6 Fe 0.4 PO4 / C
[0133] In this example, the molar ratio of Mn:Fe was fixed at 0.6:0.4, the types of pH adjusters, manganese source compounds, iron source compounds, phosphorus source compounds, sulfate radical source compounds used were changed, and the molar ratio of Mn:Fe:P:S was changed (see Table 1 for specific settings), and the other operations were consistent with Example 1. Mn 0.6 Fe 0.4 PO4·H2O precursor and its LiMn 0.6 Fe 0.4 PO4 / C were prepared, and the prepared Mn 0.6 Fe 0.4 PO4·H2O and its LiMn 0.6 Fe 0.4PO4 / C cathode materials were characterized in the same way as Example 1.
[0134] Table 1: Settings of different pH adjusters, raw materials and their ratios (Mn:Fe molar ratio fixed at 0.6:0.4)
[0135]
[0136] The Mn 0.6 Fe 0.4 PO4·H2O precursors prepared under each setting condition in Table 2 were characterized by SEM and XRD, and the results showed that they all presented micron-sized particles formed by agglomeration of nanoparticles, with similar morphology as Figure 2 (a)-2(c), and the XRD patterns all indicated that they belonged to monoclinic C2 / c space group (consistent with Figure 2 (d)), with pure phase. The LiMn 0.6 Fe 0.4 PO t / C cathode materials prepared from these precursors also presented nanoparticle agglomerates, with similar morphology as Figure 2 (e)-2(g), and the XRD patterns all indicated that they belonged to orthorhombic Pmna space group (consistent with Figure 2 (h)), and the relevant physicochemical properties and electrochemical performance data are shown in Table 2.
[0137] Table 2: Properties of Mn 0.6 Fe 0.4 PO4·H2O and LiMn 0.6 Fe 0.4 PO4 / C prepared under the conditions in Table 1
[0138]
[0139] From the results in Table 2, it can be seen that even if the types of pH adjusters, manganese sources, iron sources, phosphorus sources, sulfate radical source compounds used and the molar ratios of raw materials are adjusted within a certain range, the “oxidation-locking-release based on sulfate radicals” strategy proposed by the present application can still successfully prepare Mn 0.6 Fe 0.4 PO4·H2O precursors close to the theoretical target composition, and the LiMn 0.6 Fe 0.4 PO4 / C cathode materials prepared from these precursors all exhibit good electrochemical performance. Specifically, the manganese content of the precursors is between 18.4-19.5wt%, the iron content is between 13.8-15.3wt%, the crystallization water content fluctuates between 11.1-12.3wt%, the P / (Mn+Fe) molar ratio is between 0.99-1.04, all close to the theoretical values. The corresponding LiMn 0.6Fe 0.4 The 1C initial discharge specific capacity of the PO4 / C material is between 135-142 mAh / g, and the capacity retention after 200 cycles is between 90-93%. These results fully show that the method of the present application has good universality and robustness for raw material selection and ratio.
[0140] Example 3: Effect of different precipitation reaction condition parameters on Mn 0.6 Fe 0.4 PO4·H2O and LiMn 0.6 Fe 0.4 PO4 / C performance
[0141] This example aims to investigate the effect of changing the reaction condition parameters of steps S2 to S4 on the prepared Mn 0.6 Fe 0.4 PO4·H2O precursor and the prepared LiMn 0.6 Fe 0.4 PO4 / C (calcination conditions same as Example 1 (2): 350°C pre-calcination for 2h, 650°C final calcination for 10h) electrochemical performance.
[0142] The specific reaction condition parameter settings are shown in Table 3, and the corresponding prepared Mn 0.6 Fe 0.4 PO4·H2O precursor and the prepared LiMn 0.6 Fe 0.4 The electrochemical performance of the PO4 / C positive electrode material is shown in Table 4.
[0143] Table 3: Different reaction condition parameter settings
[0144]
[0145] The prepared Mn 0.6 Fe 0.4 PO4·H2O precursor was characterized by SEM and XRD, and the results showed that they all presented micron-sized particles formed by agglomeration of nanoparticles, and the morphology was similar to Figure 2 (a)-2 and the XRD patterns all indicated that they belonged to monoclinic C2 / c space group (consistent with Figure 2 (d)), and the phase was pure. The LiMn0.6 Fe 0.4 PO4 / C positive electrode material also exhibits a nanoparticle agglomerate, and the morphology is similar to that of Figure 2 (e) and (g), and the XRD patterns of all of them indicate that they belong to the orthorhombic Pmna space group (consistent with (h)). The relevant physicochemical properties and electrochemical performance data are shown in Table 4. Figure 2
[0146] Table 4: Mn 0.6 Fe 0.4 PO4·H2O and Li Mn 0.6 Fe 0.4 PO4 / C properties
[0147]
[0148] From Table 4, it can be seen that even if the process parameters are adjusted within a wide range (for example, the pH value in the oxidation-locking step S2 is from <0.5 to 2.0, the temperature is from 60°C to 100°C, and the time is from 0.2 hours to 2 hours; the pH value in the releasing step S3 is from 1.0 to 2.5, the temperature is from 60°C to 100°C, and the time is from 0.5 hours to 3 hours; the pH value in the crystallization step S4 is from 1.0 to 2.5, the temperature is from 60°C to 100°C, and the time is from 2 hours to 12 hours), Mn 0.6 Fe 0.4 PO4·H2O precursors close to the theoretical target composition can be effectively prepared, and the LiMn 0.6 Fe 0.4 PO4 / C positive electrode materials prepared therefrom all exhibit good electrochemical performance. Specifically, the manganese content of the precursors is between 18.2-19.2wt%, the iron content is between 13.6-14.3wt%, the crystallization water content is between 11.5-12.8wt%, and the P / (Mn+Fe) molar ratio is between 0.96-1.01. The corresponding LiMn 0.6 Fe 0.4 PO4 / C materials have a 1C initial specific discharge capacity of 134-143mAh / g, and a capacity retention rate of 90-93% after 200 cycles. These results fully demonstrate that the present application has good process robustness and can be realized within a wide process window.
[0149] Example 4: Preparation of Mn 1-x Fe x PO4·H2O precursors with different manganese-iron ratios (x value) and the performance of the corresponding LiMn 1- x Fe x PO4 / C
[0150] This example is intended to investigate the applicability of the method of the present application in preparing Mn 1-x Fe x PO4·H2O precursors with different x values. For this purpose, only the molar ratio of Mn source and Fe source in the initial charge was changed, and other conditions were consistent with Example 1, to obtain Mn 1-x Fe x PO4·H2O precursors with different x values (0 < x ≤ 0.5), wherein x ranges from 0.1 to 0.5. At the same time, according to different x values, the final calcination temperature (the pre-burning condition is still 350℃, 2h, and the heating rate is 5℃ / min) for the subsequent preparation of LiMn 1-x Fe x PO4 / C positive electrode material was adjusted (generally, the larger the x value, the higher the Fe content, and the relatively higher final calcination temperature is required to ensure sufficient crystallization and reaction, and the holding time is 10h). The physicochemical properties of the obtained Mn 1-x Fe x PO4·H2O precursors with different x values and the corresponding LiMn 1-x Fe x PO4 / C positive electrode materials were summarized in Table 5.
[0151] Table 5: Properties of Mn 1-x Fe x PO4·H2O and LiMn 1-x Fe x PO4 / C with different molar ratios of Mn and Fe (x)
[0152]
[0153] The Mn 1-x Fe x PO4·H2O precursors prepared in this example under different x values (0.1 ≤ x ≤ 0.5) were characterized by SEM and XRD, and the results showed that they all presented micron-sized particles formed by agglomeration of nanoparticles, and the morphology was similar to Figure 2 (a)-2(c), and the XRD patterns all indicated that they belonged to monoclinic C2 / c space group (consistent with Figure 2 (d)), and the phase was pure. The manganese content, iron content and crystalline water content varied within the theoretical range according to the different x values, and the molar ratio of P / (Mn+Fe) was between 0.98-1.00, indicating that the stoichiometric control was accurate. The LiMn 1-x Fe x PO4 / C positive electrode materials prepared from these precursors also showed micron-sized particles formed by agglomeration of nanoparticles, and the morphology was similar to Figure 2(e)-2(g) were similar, and the XRD patterns showed that they all belonged to the orthorhombic Pmna space group (consistent with Figure 2 (h) were consistent). The 1C initial discharge specific capacity was between 127-151 mAh / g, and the capacity retention after 200 cycles was between 90-97%.
[0154] Example 5: Mn 1-x Fe x PO4.H2O precursor under different calcination conditions to prepare LiMn 1-x Fe x Performance of LiMn
[0155] Mn 1-x Fe x PO4.H2O and the calcination conditions of Table 6 to prepare LiMn 1-x Fe x PO4 / C, to investigate the influence of the calcination conditions of the method of the present application on the performance of LiMn 1-x Fe x PO4 / C composition, structure and electrochemical performance, to show that the method of the present application is suitable for preparing Mn 1-x Fe x PO4.H2O to prepare LiMn 1-x Fe x PO4 / C.
[0156] Table 6: Calcination conditions for preparing LiMn 1-x Fe x PO4 / C
[0157]
[0158] LiMn 1-x Fe x PO4 / C prepared according to Table 6 were tested by XRD, SEM and electrochemical performance (Table 7). LiMn 1-x Fe x PO t / C cathode material also showed micron-sized particles formed by agglomeration of similar nanoparticles, belonging to the orthorhombic Pmna space group (consistent with Figure 2 (e)-2(g) were similar, and the XRD patterns showed that they all belonged to the orthorhombic Pmna space group (consistent with Figure 2 (h) were consistent). The 1C initial discharge specific capacity was between 127-151 mAh / g, and the capacity retention after 200 cycles was between 90-97%.
[0159] Table 7: Properties of LiMn 1-x Fe x PO4 / C prepared according to the conditions of Table 6
[0160]
[0161] These results fully demonstrate that the "oxidation-locking-releasing" strategy proposed by the present application is suitable for preparing high-quality manganese iron phosphate hydrate precursors with different manganese iron ratios, and LiMn 1-x Fe x PO4 / C series positive electrode materials all exhibit excellent electrochemical performance, especially when the x value is high (such as x = 0.4-0.5), very excellent specific capacity and cycle stability can be obtained.
[0162] The above examples are only some preferred schemes of the present application, and do not limit the scope of the present application in any form. Those skilled in the art should understand that, without departing from the core concept and basic principles disclosed by the present application, various forms of modification, combination, replacement or improvement can be made based on the above teachings, such as the specific selection of sulfate radical source compounds, the numerical selection and optimization adjustment of specific parameters in each process step (such as the concentration of raw materials, the pH value range and adjustment method, the temperature range, the reaction / crystallization time, the stirring rate, the washing method, the drying condition, etc.), and the application of the technical scheme of the present application to the preparation of other transition metal phosphate hydrate precursors with similar structures, etc., which should all fall within the protection scope defined by the claims of the present application.
Claims
1. A method for preparing manganese iron phosphate hydrate based on sulfate radicals, characterized in that, Includes the following steps: S1: Dissolve the manganese source compound, iron source compound, phosphorus source compound and sulfate radical source compound in water to obtain a reaction solution; S2: After adjusting the pH of the reaction solution in step S1 to acidic, heat it to carry out the reaction, and obtain a reaction solution containing an intermediate complex. S3: After adjusting the pH of the reaction solution of the intermediate complex obtained in step S2 to 1-3, heat and continue the reaction to obtain a reaction solution with precipitate; S4: Perform solid-liquid separation on the reaction liquid with precipitate obtained in step S3 and collect the precipitate; The precipitate was washed with deionized water and then redispersed in a phosphoric acid solution with a pH of 1-3 to obtain a suspension. The temperature of the suspension was then controlled at 60-100℃, and crystallization and maturation were carried out under stirring conditions. S5: Perform solid-liquid separation on the suspension after crystallization and ripening in step S4. Wash and dry the separated crystal precipitate to obtain manganese iron phosphate hydrate (Mn). 1-x Fe x PO4·H2O(0 <x≤0.5)。 2. The method for preparing manganese iron phosphate hydrate based on sulfate radicals according to claim 1, characterized in that, The manganese source compound in step S1 is selected from at least one of manganese sulfate, manganese halide, and manganese acetate; the iron source compound is selected from at least one of ferrous sulfate, ferrous halide, and ferrous acetate; the phosphorus source compound is selected from at least one of phosphoric acid, monoammonium phosphate, and diammonium phosphate; and the sulfate radical source compound is selected from at least one of sodium persulfate, ammonium persulfate, and potassium persulfate.
3. The method for preparing manganese iron phosphate hydrate based on sulfate radicals according to claim 1, characterized in that, In step S1, the molar ratio of Mn, Fe, P, and S derived from the sulfate radical source compound in the reaction solution is Mn:Fe:P:S = (1-x):x:(1.0-1.5):(1.0-2.0), where 0 <x≤0.5。 4. The method for preparing manganese iron phosphate hydrate based on sulfate radicals according to claim 1, characterized in that, The heating temperature in step S2 is 60-100℃.
5. The method for preparing manganese iron phosphate hydrate based on sulfate radicals according to claim 1, characterized in that, The heating temperature in step S3 is 60-100℃.
6. The manganese iron phosphate hydrate prepared by the method for preparing sulfate radical-based manganese iron phosphate hydrate according to any one of claims 1 to 5.
7. The manganese iron phosphate hydrate prepared by the method for preparing sulfate radical-based manganese iron phosphate hydrate according to any one of claims 1 to 5 is used as a precursor in the preparation of cathode materials for lithium-ion batteries.
8. The application according to claim 7, characterized in that, The positive electrode material of the lithium-ion battery is LiMn. 1-x Fe x PO4 / C or NaMn 1-x Fe x PO4 / C composite cathode material, in which 0 <x≤0.5。 9. A method for preparing a LiMn 1-x Fe x PO4·H2O (0 < x ≤ 0.5) as a composite cathode material for lithium-ion batteries, characterized in that, 1-x Fe x PO4 / C composite cathode material, characterized in that, Includes the following steps: ①The manganese iron phosphate hydrate, lithium source compound and carbon source prepared by the method for preparing manganese iron phosphate hydrate based on sulfate radical as described in any one of claims 1 to 5 are mixed to obtain a mixed powder; Manganese iron phosphate hydrate and lithium source compound were prepared according to a Li:(Mn+Fe) molar ratio of (1-1.1):
1. The lithium source compound is selected from either LiOH·H2O or Li2CO3; The carbon source is one or more of carbon nanotubes (CNTs), conductive carbon, sucrose, and glucose, and the amount added is 3-30 wt% of the sum of manganese iron phosphate hydrate and lithium source compound. ②The mixed powder in step ① is subjected to segmented high-temperature roasting under an inert or reducing atmosphere. After the roasting is completed, the product is naturally cooled to room temperature in an inert atmosphere, and the LiMn 1-x Fe x PO4 / C (0 < x ≤ 0.5) composite cathode material is obtained.
10. The LiMn alloy of a lithium-ion battery according to claim 9 1-x Fe x The method for preparing PO4 / C composite cathode material is characterized by, Step ②, segmented high-temperature roasting, is detailed below: The mixed powder is heated to 300-450℃ at a uniform heating rate and then kept at that temperature for 3-12 hours. Then, heat the product to 550-800℃ at a uniform heating rate, hold it at that temperature for 10-24 hours, and then cool it down.
Citation Information
Patent Citations
Method for preparing battery grade ferromanganese phosphate
CN106981656A
Method for preparing nanoscale lithium ferric manganese phosphate material by using co-crystallization method
CN113659134A
Cited By
Micro-nano structure ferromanganese phosphate and lithium ferromanganese phosphate-carbon composite material and preparation method thereof
CN121698322A